2010
DOI: 10.1111/j.1365-2516.2010.02439.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone turnover markers and bone mineral density in children with haemophilia

Abstract: During childhood growth, bone undergoes modelling involving separate osteoblastic and osteoclastic processes. Markers of bone turnover circulate at high concentrations, parallel the childhood growth curve and correlate with height velocity. The aim of this study was to compare serum markers of bone turnover in children with haemophilia and normal bone mineral density (BMD) vs. those with low BMD. In a cross-sectional study, 69 children with haemophilia were evaluated, 45 children with normal spine BMD vs. 24 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 29 publications
(38 reference statements)
4
30
0
Order By: Relevance
“…Our results were compatible with previous studies [23,24]. In a study conducted by Tlacuilo-Parra et al [25], the authors suggested that low osteocalcin levels predominated in the group with low BMD, which indicates a diminished osteoblastic bone formation activity.…”
Section: Discussionsupporting
confidence: 95%
“…Our results were compatible with previous studies [23,24]. In a study conducted by Tlacuilo-Parra et al [25], the authors suggested that low osteocalcin levels predominated in the group with low BMD, which indicates a diminished osteoblastic bone formation activity.…”
Section: Discussionsupporting
confidence: 95%
“…This suggests that haemophilia, because of its physiopathology or complications from the disease itself like arthropathy, favours abnormal bone loss . This study showed that haemophilic patients with arthropathy are more likely to have LBMD, similar to findings by Tlacuilo‐Parra et al, and Wells et al among others …”
Section: Discussionsupporting
confidence: 90%
“…Interpreting DXA results by age with either T ‐ or Z ‐score, the present study showed that patients younger than 50 years with haemophilia have a 2.65 times higher risk of LBMD when compared to healthy participants. This result is similar to findings by Tlacuilo‐Parra et al in a matched case‐control study of 62 participants in Mexico . There was no significant difference in BMD in participants 50 years or older; however, the low number of patients (n = 7) included in this age group may have limited the statistical power to detect significant differences.…”
Section: Discussionsupporting
confidence: 89%
“…Similar prevalence levels have been reported in younger men with haemophilia and worryingly reduced BMD has also been observed in children with severe haemophilia , although initiating prophylaxis before the age of 3 years may result in BMD levels comparable to persons without haemophilia . It is thought that early prophylaxis encourages greater participation in physical activity and thus maintenance of normal bone density.…”
Section: Physical Function In the Older Person With Haemophiliasupporting
confidence: 65%